Determinants of fruit and vegetables consumption among adults in Perth, Western Australia - Pollard, Christina Mary (Curtin University, 2008)
Regular consumption of adequate amounts of fruits and vegetables may be protective against chronic disease such as cardiovascular diseases, stroke, and some cancers. Inadequate consumption of fruit and vegetables is a major risk factor contributing to 1.8% of the worldwide burden of disease, with Australian estimates at 2.7%. Dietary guidelines encourage eating patterns to reduce the risk of diet-related disease and improve population well being. They provide the context for most nutrition education initiatives. Increasing fruit and vegetable consumption is a core component of most dietary guidelines.The World Health Organization (WHO) and Food and Agricultural Organization asked nations to conduct targeted campaigns to increase consumption of fruit and vegetables. Effective health communications have the capacity to increase awareness and knowledge and induce long-term changes in individual and social behaviours. There is a lack of published information about population-based interventions promoting fruit and vegetable consumption. In addition, information about the factors influencing fruit and vegetable consumption is required to assist the development of effective interventions to promote increased consumption. Demographic, individual, and environmental factors are associated with fruit and vegetable consumption.The Department of Health in Western Australia aimed to increase the prevalence of healthy eating habits consistent with Australian Dietary Guidelines. The Department developed and implemented the Go for 2&5® population based campaign to increase awareness of the need to eat more fruit and vegetable consumption between 2002 and 2005. Effective fruit and vegetables communication campaigns reach the target audience via a number of pathways including point-of-sale promotions developed by industry partners. Health professionals, industry and consumers need resources to assist food selection. Specific nutrition and recipe criteria consistent with Australian Dietary Guidelines were developed to assist industry to conduct Go for 2&5® promotions at point-of-sale.Attitudes, beliefs and behaviours relating to fruit and vegetable intake were monitored with the 1995, 1998, 2001 and 2004 Nutrition Monitoring Surveys (NMS), the Health & Wellbeing Surveillance System (HWSS) from 2001 to 2006, and the Campaign Tracking Surveys (CTS) from 2002 to 2006.Analysis of the CTS and the HWSS found that the Go for 2&5® campaign was successful in reaching the target audience and increased awareness of the recommended serves of fruit and vegetables. There was a 0.8 serve population net increase in the mean number of serves of fruit and vegetables per day over three years (0.2 for fruit (1.6 in 2002 to 1.8 in 2005) and 0.6 for vegetables (2.6 in 2002 to 3.2 in 2005)) significant at (p<0.05)). Social marketing campaigns are an effective method to increase awareness of dietary recommendations and to motivate dietary behaviour change. Monitoring changes over time showed the importance of implementing social marketing campaigns over an extended period so that incremental growth in knowledge, intentions and behaviour can occur and be maintained.Analysis of the NMS observed changes in knowledge, attitudes and some behaviours relating to fruit and vegetable intake between 1995 and 2004. In 2004, respondents were more likely to report two servings of fruit/day (OR 3.66, 95% CI=2.85, 4.70) and five servings of vegetables/day (OR 4.50, 95% CI=3.49, 5.80) as optimum compared to 1995. However, vegetable consumption (in cups) in 2004 remained less than in 1995 (RR=0.88, 95% CI=0.82 to 0.96, p=0.003). Perceived adequacy of vegetable (59.3%) or fruit (34.5%) intake, and insufficient time for vegetable preparation (14.3%) remained the main barriers to a healthy diet.A population based nutrition campaign intervention based on the fruit and vegetable dietary guideline message was associated with changes in knowledge, attitudes and some behaviours relating to fruit and vegetable consumption in Western Australian adults. Further analysis and research to assess the impact of other individual, socioeconomic and environmental factors associated with fruit and vegetable consumption is recommended.